Efficacy of Bioagents and Fungicide in Controlling Powdery Mildew of Ber (Indian Journal of Arid Horticulture, 2025)
Ber (Ziziphus mauritiana Lamk.) is an ancient fruit crop, often considered a "poor man's fruit," widely cultivated in semi-arid and arid regions of India and a few other countries due to its hardy nature. Powdery mildew, caused by Oidium erysiphoides f. sp. ziziphi, is a major disease affecting ber production in India (Kapoor et al., 1975; Gupta et al., 1978; Yadav et al., 1981), leading to significant losses in both yield and fruit quality (Prakash, 1984; Rawal, 1988). The disease was first reported in Allahabad (Mitter & Tandon, 1930), with further occurrences noted in Indian arid zones (Kumar et al., 1978).The fungus produces a whitish, powdery mass of spores on all aerial parts of the plant, leading to premature flower bud and fruit drop (Rawal, 1988). Infected fruits show discoloration, cracking, and mummification, failing to develop properly. As ber orchards continue to expand, effective disease management strategies are essential to sustain productivity and fruit quality.The use of bioagents for powdery mildew control is still limited in many crops. Therefore, this study was conducted to evaluate the efficacy of bioagents in combination with effective fungicides for the management of powdery mildew in ber.
Keywords: Ziziphus mauritiana; powdery mildew; bioagents; fungicide; disease management